Karakteristik Pemangsaan Larva Ischiodon sp. dan Coccinella sp. terhadap Rophalosiphum maidis pada Kondisi Laboratorium - Widyanto, Hery; Mahdianto, Choirul; Rahmah, Siti (Seminar Nasional Lahan Suboptimal, 2024)
Widyanto, H., Mahdianto, C., & Rahmah, S. (2024). Predation characteristics of Ischiodon sp. and Coccinella sp. against rophalosiphum maidis under laboratory condition. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 768– 777). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The use of predators as biological pest control agents must consider various ecological and biological factors of the predator, one of which is the characteristics of predation which can later provide information for field applications. The aimed of this study was to observe the characteristics of predation of several types of predators on the density of Rophalosiphum maidis prey. This study was conducted using three types of predators, namely Ischiodon sp. larvae, larvae and adult of Coccinella sp. with 5 levels of prey abundance, namely 5, 10, 15, 20 and 25 aphids. The observations made were the duration of searching and handling prey and the functional response of each predator tested. The results showed that the searching and handling time of prey by the three predators increased as the abundance of the prey population increased. Functional responses of predator larvae Ischiodon sp., larvae and imago Coccinella sp. to prey density level treatments varied based on observation time, the type of functional response was the linear type (1st type), exponential type (2nd type) and sigmoid type (3rd type). The predation ability of the three types of predators on aphids increased along with the increase in prey population and observation time. Ischiodon sp. larvae and the adult of Coccinella sp. more effective compared to the larvae of Coccinella sp. in preying on aphids because they have a faster searching and handling time along with increasing prey density.